If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-7(x-8)+2=58
We move all terms to the left:
-7(x-8)+2-(58)=0
We add all the numbers together, and all the variables
-7(x-8)-56=0
We multiply parentheses
-7x+56-56=0
We add all the numbers together, and all the variables
-7x=0
x=0/-7
x=0
| (8x-11)1/10=1 | | −4x−8−2x+5=31 | | F(0)=2^n | | 35x=31x+40 | | 2x-10+3=13 | | 7-7m=-13 | | −4−8−2x+5=31 | | 2^x=8^3+5x | | F(6)=10^n | | 2/90=x/54 | | 3/14=h/18 | | F(4)=3^n | | 5+6x=2+3x+7 | | 5x+25=4(x-1) | | 3-5/2x=6 | | (20-2x)*(20-2x)=0 | | x-8(x-2)=28-5x | | x/5-1/3=2/15 | | 2/3b+5=20-b | | F(2)=5^n | | 3+3=-2(3x-3) | | 8x+3(2x-4)=3(x-6) | | 7=p+10 | | 6/b=8/3 | | -3n-21=-18 | | 6.6x+9.8=16.1x+9.8 | | 6(1-8r)=-7r+6 | | J(×)=2x+9 | | .14=3x-2 | | 5x-6+x+2=-5x+6-15 | | 2w^2+21w+10=0 | | 8(6x+10)=-8 |